2022
DOI: 10.1111/1471-0307.12906
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and microbiological stability and sensorial properties of traditional Iranian butter incorporated with pomegranate peel extract

Abstract: In this study, the antioxidant activity of pomegranate peel extract (PPE) and its potential effect on the chemical and microbiological stability of traditional butter was investigated. The PPE having total phenol content of 327.48 AE 1.43 mg gallic acid equivalent/g showed significantly greater (64.34 AE 0.32%) radical scavenging activity than butylated hydroxy toluene. Butter treated with PPE had significantly lower levels of peroxide value, free fatty acids, Totox, Schaal value and microbial population. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…However, in PP-SYS4, the microbial load significantly decreased ( p ≤ 0.05) by 37% compared to the control after 2 months of cold storage ( Figure 8 ). Ebrahimain et al [ 83 ] studied microbiological stability and sensory properties of traditional Iranian butter with pomegranate peel extract incorporated into it, and they found that PPE could reduce the bacterial count in butter from 9.25 log CFU to 6.30 log CFU after 90 days of storage, while with increasing storage time, the total number of bacteria was increased in the treatments; this increase is most evident when dairy products are made with poor safety quality.…”
Section: Resultsmentioning
confidence: 99%
“…However, in PP-SYS4, the microbial load significantly decreased ( p ≤ 0.05) by 37% compared to the control after 2 months of cold storage ( Figure 8 ). Ebrahimain et al [ 83 ] studied microbiological stability and sensory properties of traditional Iranian butter with pomegranate peel extract incorporated into it, and they found that PPE could reduce the bacterial count in butter from 9.25 log CFU to 6.30 log CFU after 90 days of storage, while with increasing storage time, the total number of bacteria was increased in the treatments; this increase is most evident when dairy products are made with poor safety quality.…”
Section: Resultsmentioning
confidence: 99%
“…The use of organic by-products as preservatives showed better results than the chemical food preservatives along with lesser side effects. Fortification of butter with pomegranate peel extract not only showed enhanced antioxidant properties but also low levels of free fatty acids and microbes, thus proving it to be a good bio-preservative for butter (Ebrahimian et al, 2023).…”
Section: Milk and Milk Productsmentioning
confidence: 99%
“…The use of organic by‐products as preservatives showed better results than the chemical food preservatives along with lesser side effects. Fortification of butter with pomegranate peel extract not only showed enhanced antioxidant properties but also low levels of free fatty acids and microbes, thus proving it to be a good bio‐preservative for butter (Ebrahimian et al., 2023 ). One of the additional benefits of using pomegranate peel extract in milk products is that in combination with probiotics, it effectively lowers the levels of triglycerides and reduces intracellular lipid accumulation (Figure 2 ).…”
Section: Food Applicationsmentioning
confidence: 99%
“…Dairy products are susceptible to contamination and, therefore, pose a risk to consumer health due to their relatively short shelf life [ 66 ]. Microbial spoilage in these products can be delayed by using food-based extracts because of their phytochemical contents and antioxidant and antimicrobial activities [ 51 , 52 , 53 , 54 ].…”
Section: Application Of Natural Antimicrobialsmentioning
confidence: 99%